Linguistic Politeness: A Pragmatic Analysis of the Request Letters - Basis, Aljhem (International Journal of Language and Literary Studies, 2024)
The objectives of this study are: discover the linguistic features in the opening strategy, closing strategy, and directness of the head-acts in the request letters; identify and analyze positive and negative politeness strategies used in request letters sent by students, organizations, and companies to the office of the Dean of Student Affairs; investigate the use of politeness strategies that indicates about linguistic conventions. This study employed a mixed-methods research design, incorporating both quantitative and qualitative analyses. The primary data for this study consists of request letters from students at St. Vincent's College Incorporated and various organizations within and outside the academic institution. The researcher selected 15 request letters submitted to the Dean of Student Affairs Office during the 2021-2022 academic year. This study employed three tiers of corpus analysis. The research reveals that request letters sent to the Dean of Student Affairs Office at the institution employ a diverse range of politeness strategies. The "other complimentary close and other pre-closing" is another element of the closure strategy that the researcher discovered. The head-acts shown that request letters are often direct on a degree of directness. The utilization of politeness strategies within a broader socio-cultural context illuminates established linguistic norms. The diverse inclinations towards employing politeness strategies and their multifaceted applications in request letter communication do not necessarily indicate a transition from impoliteness to politeness or vice versa. It demonstrates that people's communication styles and methods of politeness are evolving.